2022
DOI: 10.1155/2022/5777106
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Peripheral Blood miR-181c, miR-101, and Cognitive Impairment in Patients with Diabetes Mellitus Complicated with Acute Stroke

Abstract: Objectives. To explore the relationship between peripheral blood microRNA-181c (miR-181c), microRNA-101 (miR-101), and cognitive impairment (CI) in patients with diabetes mellitus (DM) complicated with acute stroke (AS). Methods. A retrospective analysis was performed on 70 patients with DM complicated with AS admitted to the hospital between January 2019 and December 2021. According to presence or absence of CI, they were divided into CI group (41 cases) and non-CI group (29 cases). The clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…65 Furthermore, miR-181 has been linked to diabetic cardiovascular complications. [66][67][68][69] Hydrogen peroxide (H 2 O 2 ) markedly increased miR-181a expression in the H9C2 rat cardiomyocytes and regulated the mitochondrial apoptotic pathway by targeting glutathione peroxidase-1 (GPx1), a pivotal intracellular antioxidant enzyme. 70 MiR-181a-5p was involved in hypoxia-reoxygenation-induced cardiomyocyte apoptosis by targeting sirtuin 1 (SIRT1).…”
Section: Mir-181 In Cardiomyopathy and Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…65 Furthermore, miR-181 has been linked to diabetic cardiovascular complications. [66][67][68][69] Hydrogen peroxide (H 2 O 2 ) markedly increased miR-181a expression in the H9C2 rat cardiomyocytes and regulated the mitochondrial apoptotic pathway by targeting glutathione peroxidase-1 (GPx1), a pivotal intracellular antioxidant enzyme. 70 MiR-181a-5p was involved in hypoxia-reoxygenation-induced cardiomyocyte apoptosis by targeting sirtuin 1 (SIRT1).…”
Section: Mir-181 In Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…examined the expression of peripheral blood miRNAs in young healthy controls, aged healthy controls, and age‐matched HF patients and reported that miR‐181 family members' expression was reduced in aged individuals and further reduced in age‐matched HF patients 65 . Furthermore, miR‐181 has been linked to diabetic cardiovascular complications 66–69 . Hydrogen peroxide (H 2 O 2 ) markedly increased miR‐181a expression in the H9C2 rat cardiomyocytes and regulated the mitochondrial apoptotic pathway by targeting glutathione peroxidase‐1 (GPx1), a pivotal intracellular antioxidant enzyme 70 .…”
Section: Mir‐181 In Cardiovascular Diseasementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%